Unveiling the intricacies: small interfering RNA targeting Snail-1 unravels dynamics in endometrial carcinoma cell behavior - Li, Feng; Zhi, Yuanyuan; Wang, Yinghui; Hussain, Shaik Althaf; Alrubie, Turki Mayudh; Yang, Ping (Frontiers in Oncology, 2025)
BackgroundInvestigated within the endometrial carcinoma (EC) context, Snail-1 emerges as a pivotal transcription factor governing invasion and metastasis by orchestrating epithelial-to-mesenchymal transition (EMT). Employing small interfering RNA (siRNA) to silence Snail-1 expression in the HEC-1A cell line, this study explored the repercussions on the expression of genes implicated in metastasis, cellular cytotoxicity, apoptosis, and migration.MethodsHEC-1A cells were transfected with Snail-1-specific siRNA. Quantitative Real-time PCR was utilized to quantify the mRNA levels of Snail-1, Matrix metalloproteinase-9 (MMP-9), Vimentin, E-cadherin, Notch1, ERK, AKT, and miR-34a. Western blot analysis was also performed to ascertain alterations in Snail-1, MMP-9, Vimentin, E-cadherin, and Notch1 protein levels. Cytotoxicity of transfected cells was assessed via the MTT assay, while flow cytometry was employed to measure apoptosis. Migration was evaluated using a wound healing assay.ResultsTransfection with 60 pmol/mL of Snail-1-specific siRNA significantly reduced Snail-1 expression at both the mRNA and protein levels. This was accompanied by decreased MMP-9, Vimentin, and Notch1 expression and increased E-cadherin expression, all confirmed at both transcript and protein levels. Furthermore, gene expression analysis revealed a downregulation of ERK and AKT mRNA levels and an upregulation of miR-34a. Moreover, transfection correlated with increased apoptosis and decreased migration of treated HEC-1A cells.ConclusionThe study emphasizes the significant influence of Snail-1 on EMT in EC cells, thereby impacting apoptosis and metastasis. Targeted silencing of Snail-1 through specific siRNA emerges as a promising therapeutic approach in treating EC.